Climate Change and Desertification: Biophysical Processes and' LiveliJood Interactions in the Orylands - Eriksen, Siri H (Annals of Arid Zone, 2016)
This paper reviews the biophysical and social linkages between climate change and desertification or dryland degradation. It argues that while the physical linkages are fairly well identified, it is within the emerging linkages between social processes related to climate change and desertification that some of the most effective measures can be put into place. It suggests that the underlying causes of vulnerability to both climate change and desertification include the political ecology of resource control, urbanization, and economic globalization affecting domestic markets and agricultural specialization. Particular attention is paid to using local livelihoods and vulnerability as a point of departure for measures designed to ameliorate the impacts of climate change and desertification.